Revisiting Economic Growth and Trade Openness: An Empirical Analysis of Major Trading Nations - Singh, Ram; Aftab, Areej (Journal of Comparative International Management)

(untitled) (Management Futures, 2023)
This paper considers 15 major trading nations from 1996-2018 to assess the relationship between economic growth and trade. This relationship has been governed by the nature of exports as well as the stage of development of a nation. In the present paper key macro-economic variables as identified from literature, including scale of foreign direct investment, domestic investment, exchange rates and labour productivity. The study provides unique insights as it indicates a positive relationship of all variables vis a vis economic growth of the countries except foreign direct investment. Granger causality test however indicates growth causes exports, FDI, and trade. Furthermore, there exists a bi-directional causality between labour productivity and growth as well as imports and growth. Therefore, the findings of this paper provide a reference for future economic planning and policy formulation of the selected countries.